Thermochemical conversion of Napier grass for production of renewable syngas - Md Said, Mohamad Syazarudin; Wan Ab. Karim Ghani, Wan Azlina; Tan, Hong Boon; Hussain, Siti Aslina; Ng, Denny Kok Sum (MDPI, 2019)
Fuel resource diversification is a global effort to deviate from non-renewable fossil fuels. Biomass has been identified as an alternative solid biofuel source due to its desirable properties and carbon neutrality. As reported in the literature, biomass can positively contribute towards combating climate change while providing alleviation for energy security issue. As part of efforts to diversify biomass resources, this work intends to explore the potential of Napier grass, one type of energy crop, for the production of renewable syngas via gasification. This energy crop is originally from Africa, which is highly productive with low cost (40 tonnes per year per hectare). Limited studies were conducted to analyze the potential of such an energy crop as a fuel source, which is the subject of this work. In order to analyze the full potential of such energy crop, the physical and chemical characteristics of this biomass was first analyzed. To determine the productivity of syngas from this biomass, fluidized bed gasifier was used in this work. The effects of gasification process parameters (i.e., equivalence ratio and temperature) on product yield and producer gas compositions were examined. Besides, the effects of equivalence ratio towards higher heating value of syngas and carbon conversion efficiency were analyzed. Based on the ultimate analysis results, the molecular formula of Napier gas was CH1.56O0.81N0.0043. Meanwhile, the higher heating value of such biomass was determined as 16.73 MJ/kg, which was comparable to other biomasses. It is noted that in this work, the volatile matter was determined as 85.52% and this promoted gasification process remarkably. The dynamics of the reactions involved were observed as a significant variation in product yield and biogas components were recorded at varying equivalence ratio and gasifier operating temperature.